Analisis Penerapan Akad Mudharabah pada Tabungan BMT UGT Nusantara Capem Pare Sesuai PSAK 105 - Safitri Nurul Agustin; Nina Dwi Setyaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The implementation of mudharabah agreement on sharia savings is very important to ensure the management of capital owner funds (shahibul mal) in accordance with sharia principles. To find out the application of mudharabah agreement on sharia savings, provisions are required that are in accordance with the Financial Accounting Standards Statement (PSAK) 105. This study aims to analyze in depth the mudharabah agreement protocol on sharia savings at Baitul Maal wa Tamwil (BMT) UGT Nusantara Capem Pare Kediri with the Financial Accounting Standards Statement (PSAK) 105 which is the mudharabah accounting standard. This study is a qualitative study and uses a descriptive approach. The results of this study indicate that (1) Baitul Maal wa Tamwil (BMT) UGT Nusantara Capem Pare Kediri as a fund manager has implemented a mudharabah agreement for the management of savings deposited by capital owners (shahibul mal) which are then managed for productive businesses. The profit sharing system used is 60% for BMT and 40% for members. And the distribution of results is carried out based on the agreed ratio after BMT makes a profit. (2) The analysis of PSAK 105 on the mudharabah contract for savings at BMT UGT Nusantara Capem Pare Kediri is correct in terms of recognition and measurement, but the presentation and sealing are still less than perfect, because they only cover the balance sheet, profit and loss, and cash flow, and do not follow the provisions of PSAK 101.